SPEAKING ACTIVITIES IN MADRASAH IBTIDAIYAH: A META NARRATIVE ABOUT CHARACTER BUILDING AND MULTICULTURALISM POINT OF VIEW - Kurdi, Muqarramah Sulaiman; Mardiah, Mardiah; Kurdi, Musyarrafah Sulaiman; Ghazali Usman, Muhammad Iqbal; Taslimurrahman, Taslimurrahman Taslimurrahman (UIN Sunan Kalijaga Yogyakarta, 2020)
Teaching experience of speaking skills tends to be underestimated by the teacher. Because speaking, especially in Bahasa Indonesia, is considered as the mother tongue used in pupil's daily communication. In general, madrasas ibtidaiyah teachers assume that speaking skills in Bahasa Indonesia are not so essential compared to reading and writing. Speaking skills considered to be something that has been studied by pupils since birth at home so that speaking skills are not emphasized to be taught more on the primary level. When designing the learning process, the teacher only focuses on material and students' cognitive without paying attention to student skills in conveying the context or conversation. This study aims to develop a learning activities model of speaking with the content of character building and a multicultural perspective. The researchers applied the ASSURE model as the approach to developing the learning model. The findings of this study showed that the learning model is carried out by analyzing the characteristics of students, setting learning objectives, choosing media, learning methods, and teaching materials, utilizing teaching materials, involving students in learning activities, evaluating and revising learning programs. The content of character education and multiculturalism perspective are applied as teaching material.